Application of geographic information systems to management of municipal solid waste depots in Lagos Island Local Government Area of Lagos State (2013)
The nature of socio-economic transactions taking place in Lagos Island every day makes solid waste management challenges more acute. These transactions generate large volume of waste which has become an environmental challenge because of poor refuse management strategies which do not match the rate of refuse generation. This study examines the underlying factors militating against efficient control of solid waste collection in Lagos Island by applying geographic information systems and conventional qualitative and quantitative research techniques to proffer possible solutions. A set of structured questionnaire was administered on 240 households in the six wards in Lagos Island that had waste depots to collect information on the mode of storage, transportation to communal waste depots and methods of disposal of solid waste in the area. However, only 215 copies (89%) of the questionnaire were retrieved for analysis. Digital analyses such as nearest neighbour, buffering, overlay and distance measurement were carried out with the aid of ArcMap 9.3 to reveal the geographical locations of solid waste depots, the spatial pattern of distribution, and distances covered by residents and traders to dispose solid waste. The existing 13 designated refuse depots were found to be grossly inadequate to facilitate effective evacuation of solid waste in Wards A, B, and C, while D, E, and F and G did not have waste bins. In the three wards where waste bins were provided, the distances of more than 200m between respondents’ residences and waste depots, as well as the complete absence of waste depots in others, encouraged patronage of illegal refuse collectors who disposed refuse indiscriminately. It is recommended that public awareness campaign be heightened and sustained and additional communal solid waste depots provided in Lagos Island to facilitate accessibility and reduce the distance usually covered by residents and traders to dispose refuse. This will promote prompt and healthy disposal of solid waste in Lagos Island and prevent possible incidence of enteric ailments